Genetic assessment of apolipoprotein E polymorphism and PRNP genotypes in rapidly progressive dementias in Pakistan - Urwah Rasheed; Minahil Khalid; Aneeqa Noor; Umar Saeed; Rizwan Uppal; Saima Zafar (Prion)
Rapidly progressive dementias (RPDs) are a type of fatal dementias that cause rapid progression of neuronal dysfunction. This study aimed to assess the prevalence of APOE genotypes (ε2, ε3, ε4) and PRNP mutations (E200K, M129V) in the general population of Pakistan because of their association with RPDs, including Rapidly Progressive Alzheimer’s Disease (rpAD) and Creutzfeldt-Jakob Disease (CJD). Blood samples (n = 100) were collected from healthy Pakistani population and the stated mutations were assessed using polymerase chain reaction. In the analysis of the APOE genotype, ε3/ε3 genotype was the most common (95%), followed by ε3/ε4 (5%) and ε2 allele was completely absent. A low frequency of ε4 allele and the absence of a protective ε2 allele is associated with an increased risk of rpAD. In the case of PRNP mutations, the most common genotype was M129-Ε200 (71%) and V129-Ε200 (29%). E200K mutation was completely absent from the given population. It is noteworthy that the MM homozygous genotype was present in 71 samples, VV genotype was present in 29. Homozygosity on codon 129, as observed in most of our samples, has been associated with more efficient production of PrPSc and disease pathology. This study provides preliminary data indicating that rpAD and CJD pose a significant threat to the Pakistani population.